Society's Knowledge About Physiological Causes of Hair Loss: A Cross-Sectional Study at The University of Basrah: Pengetahuan Masyarakat Tentang Penyebab Fisiologis Kerontokan Rambut: Sebuah Studi Cross-Sectional di Universitas Basrah - Al-Hejaj, Zahraa Mahmoud Hussain (Universitas Muhammadiyah Sidoarjo, 2025)
Background: About 50% of men and nearly 50% of women experience hair loss, making it one of the most prevalent aesthetic issues in the world. This condition can have a detrimental impact on each person's quality of life and can result in circumstances that can cause psychological distress and demoralization. It's critical to comprehend whether hair loss is a regular physiological process or whether it's an aberrant process brought on by issues with the scalp or its bulb, for example. Since baldness, alopecia, and all forms of hair loss are always the consequence of multiple factors that contribute to their development, defining them is frequently difficult and reductive. Objectives: To assess the knowledge about the physiological reasons that lead to hair loss and find the relationship between knowledge and socio-demographic characteristics. Material and methods: A descriptive cross-sectional study was conducted from October 10, 2024, to January 15, 2025. A random sample of 150 people from Basrah University participated in the study. To gather information and evaluate knowledge, a questionnaire was employed. Results: Most of the university population is not sure that Cushing's syndrome does not cause hair loss (44.7%), most of the university population agree Hyperthyroidism causes hair loss (76.7%), most of the university population agree Vitamin D deficiency causes hair loss (89.3%), The majority of university students concur that there is a connection between ferritin insufficiency and hair loss (40.7%), while the majority of students concur that there is a connection between zinc deficiency and hair loss (71.3%). However, half of the students disagree. The majority of university students believe that iron deficiency and hair loss are related (84.7%), that obesity causes hair loss (50%), and that heredity does not cause hair loss (76.7%). Additionally, the majority of university students (70%) concur that there is a connection between vitamin A insufficiency and hair loss, and over half (55.3%) concur that there is a connection between biotin shortage and hair loss, more than half of college students (57.3%) concur that folic acid deficiency and hair loss are related. Conclusion: According to the results of this study, most university students are well-informed about hair loss. Highlights: air loss affects 50% of men and women, impacting quality of life. Objectives: Assess knowledge on physiological causes of hair loss and socio-demographics. Conclusion: Most university students are well-informed about hair loss causes. Keywords: Society, Physiological, Hair loss, Vitamin D, knowledge